Permanent Fixation of Radially Compressed Bamboo in Dry Condition by Heating and Its Mechanism - Bambang Subiyanto; Wahyu Dwianto; Takashi Higashihara; Toshiro Morooka; Misato Norimoto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
The stress-strain relationship and stress relaxation of oven-dried bamboo in radial compressed by heating were investigated. The effect of heating temperature and time on the weight loss, residual stress and strain recovery were also examined. The results indicated that the apparent of stress-strain curve (SS-curve) of Indonesian bamboo was different with Mousou bamboo and Sugi wood. The apparent SS-curve of Mousou bamboo was same as general SS-curve of wood under heating. The effect of heating temperature on yield stress of oven-dry bamboo had different results with the Sugi wood. The yield stress of bamboo decreased slightly up to heating temperature of 140 °C, then it was significantly decreased with increasing temperature. The decreasing yield stress of bamboo at heating temperature above 140 °C could be due to degradation or decomposition of existing extractive component and hemicelluloses in bamboo by heating. Time to achieve stress relaxation decreased with increasing heating temperature. The stress relaxation of bamboo was attained faster than that of Sugi wood. Tali bamboo had a fastest to attain stress relaxation than others type of bamboo. The residual stress and strain recovery decreased with decreasing weight loss. The most interesting finding was residual stress of Indonesian bamboo (Gombong and Tali bamboos) was attained zero and stress recovery less than 0.2 when the weight loss at about 4%.Key words: bamboo, permanent fixation, stress-strain.